Prevalence and Severity of Poststroke Depression among Stroke Survivors in Northeastern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Post stroke depression (PSD) is a common neuropsychiatric mood disorder believed to be under-diagnosed among stroke survivors.Objective:The aim of this study was to determine the prevalence and severity of PSD among stroke survivors in north-eastern Nigeria.Materials and Methods:A purposive sample of stroke survivors (N= 249) in six tertiary health institutions in north-eastern Nigeria completed a three-part survey. Part 1 elicited sociodemographic information and part 2 was a Patient Health Questionnaire-9, utilized to identify the presence of PSD and its severity, while part 3 was Barthel Index utilized to determine the level of independence of participants. Chi-square test was used to determine the difference in prevalence of PSD between gender, different occupational statuses, living conditions, previous history of stroke, and side of hemispheric lesion. Pearson product moment correlation coefficient was used to determine the relationship between depression and age, duration of stroke, and level of independence.Results:An overwhelming majority of the participants (93.6%) were depressed; females tend to be more depressed (P< 0.05) than males. Significant correlation was observed between age and level of independence and PSD (r= −0.157,P= 0.013 andr= 0.345,P< 0.001, respectively). However, there was no significant correlation between the duration of stroke and PSD (r= −0.111,P= 0.079).Conclusion:This study revealed a high prevalence of PSD in the study region with females being more at risk. Further, increase in age and decreased level of independence correlated with PSD.